Quantification and Characterization of Phenolic Compounds from Northern Indian Propolis Extracts and Dietary Supplements. (21st March 2020) - Avula, Bharathi; Sagi, Satyanarayanaraju; Masoodi, Mubashir H; Bae, Ji-Yeong; Wali, Adil F; Khan, Ikhlas A
Abstract: Background: Propolis is a resinous substance produced by bees. Propolis extracts have been used for anti-inflammatory and antimicrobial activities. The use of propolis dietary supplements has been increasing in the United States and the rest of the world. Objective: A simple, economic, and valid analytical method is needed for quality assessment of dietary supplements and extracts claiming to contain propolis. Methods: A ultra-high performance liquid chromatography (UHPLC) quadropole time-of-flight-MS method was used to characterize the chemical composition of northern Indian propolis. Fourteen major phenolic compounds were quantified using a UHPLC-DAD method. An HPTLC method was used to develop chemical fingerprinting profiles for propolis extracts and dietary supplements. The seven propolis extracts and 14 dietary supplements purchased in the U.S. were analyzed using the UHPLC-DAD-QToF method. Results: Fifty-seven compounds belonging to phenolic, coumarin, fatty acid, and terpene classes were identified in propolis extracts. Based on quantification results, the content of 14 phenolic compounds in propolis extracts varied from 19–32% in dietary supplements, a significant variation to the recommended daily intake (0.2–94 mg/day). Conclusions/Highlights: The developed analytical methods can be used for quality assessment of propolis extracts and dietary supplements.